2018
DOI: 10.14740/jocmr3344w
|View full text |Cite
|
Sign up to set email alerts
|

The Main Anatomical Variations of the Pancreatic Duct System: Review of the Literature and Its Importance in Surgical Practice

Abstract: Anatomical variations or anomalies of the pancreatic ducts are important in the planning and performance of endoscopic retrograde cholangiopancreatography (ERCP) and surgical procedures of the pancreas. Normal pancreatic duct anatomy occurs in approximately 94.3% of cases, and multiple variations have been described for the remaining 5.7%. The purpose of this study was to review the literature on the pancreatic duct anatomy and to underline its importance in daily invasive endoscopic and surgical practice. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 23 publications
1
37
0
6
Order By: Relevance
“…Türkvatan et al 8 classified the pancreatic ductal system into five types, and reported that the most common type was the MPD (type I) followed by the absent APD (type III). In the present study, type III was the predominant type, which is similar to the studies by Dawson and Langman, 2 Sunjida Shahriah et al, 3 Adibelli et al, 7 and Bülow et al 17 In a literature review on the main anatomical variations of the pancreatic duct system by Dimitriou et al, 18 a total of 8,260 patients were analyzed. In their study, 94.3% of the cases displayed normal anatomy (types I-III), 4.5% had pancreas divisum, and 1.2% were reported as having rare anomalies.…”
supporting
confidence: 88%
“…Türkvatan et al 8 classified the pancreatic ductal system into five types, and reported that the most common type was the MPD (type I) followed by the absent APD (type III). In the present study, type III was the predominant type, which is similar to the studies by Dawson and Langman, 2 Sunjida Shahriah et al, 3 Adibelli et al, 7 and Bülow et al 17 In a literature review on the main anatomical variations of the pancreatic duct system by Dimitriou et al, 18 a total of 8,260 patients were analyzed. In their study, 94.3% of the cases displayed normal anatomy (types I-III), 4.5% had pancreas divisum, and 1.2% were reported as having rare anomalies.…”
supporting
confidence: 88%
“…A widely accepted classification system for pancreatic ductal configuration recognizes five classes of ductal configuration ( Figure 2) [8].…”
Section: Pancreatic Duct Configuration Variationsmentioning
confidence: 99%
“…Types 1, 2 and 3 are regarded as 'normal' anatomy [15]. A recent systematic review that analyzed the pancreatic duct anatomy of 8,260 individuals found normal anatomy (types 1-3) in 94.3% of the cases, pancreas divisum (type 4) in 4.5%, and ansa pancreatica (type 5) in 0.25% of individuals [8].…”
Section: Figure 2: Pancreatic Duct Configurationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors call Santorini duct as regressed proximal main duct of dorsal pancreatic bud [4]. Recent review papers of pancreatic anatomy also give unclear description: "The ventral pancreatic duct and the distal part of the dorsal pancreatic duct are anastomosed and form the MPD of Wirsung, while the proximal part of the dorsal pancreatic duct becomes the APD of Santorini" [2]. This few examples show dual benchmark related to pancreatic gland.…”
mentioning
confidence: 99%